Методологические подходы к решению проблемы обучения и преподавания - Сейтқазы, З.М. (My University, 2016)
The article is sanctified to the to date issue of the day: methodologies of pedagogics in the conditions of innovative development of the educational systems. The aim of this article is a necessity of increase of professional level of teachers. Basic attention in process an author accents on perfection of informatization of educational process assisting professional development of teachers that gives an opportunity to see efficiency of the applied strategies. Main result- acquisition by the teachers of skills of application of new approaches for educating of schoolchildren. An author comes to the conclusion, that application of these strategies is the optimal method of joint permission of problems in educating.
Keywords: problem; strategy; informatization; professionalism; method